‘Disguised I’: Generalization vs Individualization - Tonyan, Marika (Armenian Folia Anglistika, 2015)
Whether one is an indefinite pronoun, which denotes no person in particular, or a generic one often synonymous to I, is a long-standing issue in semantics. In the article we present evidence in favour of one’s generic nature, and argue that the pronouns one and I, despite being referentially identical, have denotational characteristics of their own, and therefore function in different ways. The pronoun I, which is characterized by the highest level of semiotic individualization, is the basic lexical unit employed to denote the speaker, but it is by no means the only one. In all languages there are numerous ways of referring to the addresser of the message, including the employment of lexical units with generic reference. In the present paper we are going to discuss the use of one instead of I, in which the former operates as a ‘disguised I’, particularly in the speech of people holding a high position. This function of one used to be sociolinguistically marked, but in the present-day society with its emphasis on egalitarianism and political correctness, in most cases, the speaker’s choice of one is explained by his wish to sound more formal rather than more socially distinguished. However, the semantic features of this pronoun, as will be shown in the article, account for such linguistic interaction in which the use of one signalizes the existence of a certain distance between the interlocutors.